The Effect of Corn Husk Waste Addition in Paper Production on Surface Texture and Printability - Dianta Mustofa Kamal; Nadiah Tsabitah; Nayla Nazneen (Multicore International Journal of Multidisciplinary (MIJM), 2025)
Indonesia, as an agrarian country with abundant corn production, generates a significant volume of corn husk waste. This study aims to evaluate the effect of corn husk waste addition on the physical characteristics of recycled paper, particularly surface texture and print quality. Corn husk waste was selected due to its high cellulose content and wide availability in Indonesia. The papermaking process involved delignification using NaOH, bleaching with H₂O₂, and blending recycled paper pulp with corn husk fibers. The test results show that corn husk fibers increase paper thickness and tensile strength, while providing a rougher but still functional surface texture. Printing tests indicated that ink absorption remained adequate, although minor spreading was observed in rougher areas. Overall, the resulting paper has potential as an eco-friendly alternative for simple applications such as handicrafts and non-commercial printing.